What Can We Learn about the “Resource Curse” from Foreign Aid? - Morrison, Kevin M. (Oxford University Press on behalf of the World Bank, 2013)
A large body of literature has arisen in economics and political science analyzing the apparent “resource curse”—the tendency of countries with high levels of natural resources to exhibit worse economic and political outcomes. The author examines the purported causal mechanisms underlying this “curse” and shows that they all center on the revenue that these resources generate for the government. As such, it is not surprising that the most recent literature on the topic has demonstrated that, in the hands of a competent government, natural resources have no negative consequences and may actually have positive effects. The important question therefore is: What can be done in countries without effective governments? Policy proposals have centered on (a) taking the resources out of the hands of the government or (b) having the government commit to use the funds in certain ways. Neither of these has been particularly successful, which we might have predicted from research on another important nontax revenue source for developing countries: foreign aid. The close parallels between the foreign aid and “resource curse” literatures are reviewed, as are the lessons from the aid literature. These lessons suggest the need for an important change in approach toward poorly governed resource-rich countries.